2010
DOI: 10.1051/0004-6361/200912431
|View full text |Cite
|
Sign up to set email alerts
|

The Suzaku broadband X-ray spectrum of the dwarf Seyfert galaxy NGC 4395

Abstract: We present a Suzaku observation of the dwarf Seyfert galaxy NGC 4395 with an estimated black hole mass of ∼10 5 M . Rapid and strong X-ray variability with an rms amplitude of ∼60 per cent is observed in the 0.4-10 keV band with the XIS cameras. The shape of the light curve appears to depend on energies. The hard X-ray emission is detected up to 35 keV with the HXD-PIN detector at a similar flux level as observed with the INTEGRAL IBIS. The X-ray spectrum below 10 keV is strongly absorbed by partially ionized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Incidentally, it is also worth noting that the intrinsic 0.5–10 keV emission of NGC 4395 implied in this cold absorption scheme is larger than the observed one by just a factor of ∼2 (Table 1). Taking advantage of the Swift /BAT spectral constraints, the resulting 0.5–100 keV luminosity is ∼6–8 × 10 40 erg s −1 , which exceeds the usual estimates of the bolometric luminosity (see also Moran et al 2005; Iwasawa et al 2010). Depending of the exact value of the black hole mass, the Eddington ratio of NGC 4395 could be much closer to ∼0.01 than previously thought.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Incidentally, it is also worth noting that the intrinsic 0.5–10 keV emission of NGC 4395 implied in this cold absorption scheme is larger than the observed one by just a factor of ∼2 (Table 1). Taking advantage of the Swift /BAT spectral constraints, the resulting 0.5–100 keV luminosity is ∼6–8 × 10 40 erg s −1 , which exceeds the usual estimates of the bolometric luminosity (see also Moran et al 2005; Iwasawa et al 2010). Depending of the exact value of the black hole mass, the Eddington ratio of NGC 4395 could be much closer to ∼0.01 than previously thought.…”
Section: Discussionmentioning
confidence: 66%
“…2 (see e.g. the X-ray colour HR3 in Iwasawa et al 2010): again, six different periods have been identified. We have adopted the same model defined above.…”
Section: The Suzaku Observationmentioning
confidence: 97%
See 1 more Smart Citation
“…We froze the power-law spectral index at Γ = 1.8 due to the small number of counts, while still varying the normalization. Although some of the literature on NGC 4395 finds a much lower spectral index of Γ 1.5 (e.g., Lira et al 1999;Shih et al 2003;Moran et al 2005;Iwasawa et al 2010), a higher spectral index, Γ ≈ 2.0 ± 0.2, was found by Nardini & Risaliti (2011) when fitting an averaged Swift/BAT spectrum above 10 keV. This suggests that the hard spectral index at low X-ray energies is partly due to absorption and not intrinsic.…”
Section: X-raysmentioning
confidence: 98%
“…The dwarf Seyfert 1.8 galaxy NGC 4395 (d = 4.2 Mpc Karachentsev & Drozdovsky 1998) is one of the most X-Corresponding author: E. Kammoun ekammoun@umich.edu ray variable non-jetted active galactic nuclei (AGN; e.g., Iwasawa et al 2000;Vaughan et al 2005;Iwasawa et al 2010). The optical and ultraviolet (UV) spectra of this source show high-ionization forbidden lines with broad wings corresponding to gas velocities larger than ∼ 10 3 km s −1 (Filippenko & Sargent 1989), in addition to permitted lines such as C IV, Mg II, O III and Hα (see e.g., Filippenko et al 1993).…”
Section: Introductionmentioning
confidence: 99%